The social life of images. Issue 1 (1st January 2020) - Awad, Sarah H.
Abstract : This paper presents a theoretical and methodological approach to analysing images in public space as part of a transformative visual dialogue in everyday life. Images are conceptualised through the lens of sociocultural psychology and analytically approached through the metaphor of 'the social life of images, ' by which the life cycle of images is followed as they respond and borrow from one another in a continuous dialogue. The analytical framework starts by situating the image and identifying its spatial and temporal contexts. Then, it considers the social actors influencing the image's social life and the different stages in an image's trajectory. Leading to an analysis of the political dynamics of an image and its potential symbolic power to influence the public discourse. Examples from street art, online, and news images will be used to illustrate the analytical approach.